DESIGNING LEARNING ANIMATION ASSETS FOR GENIORA SAYABISA JUNIOR HIGH SCHOOL LEVEL - Aurellia, Talitha; Sugiarto, Eko (LPPM Univ. Ibn Khaldun Bogor, 2025)
The development of information technology in the era of the Industrial Revolution 4.0 has transformed learning systems into more digital ones, especially since the COVID-19 pandemic hit, leading to the implementation of distance learning. However, the lack of interaction and engaging visualizations has resulted in a decline in students understanding and interest in learning. As one of the companies operating in the education sector, Geniora offers a solution through its product SayaBisa, which is now being developed for junior high school students. This study aims to design effective animated assets as visual learning media to support educational content. The method used is practice-based research, supplemented with literature reviews and visual studies, culminating in the creation of the final work. The results indicate that animated assets not only serve an aesthetic purpose but also function as communicative and educational message-delivery tools. Thus, the designed educational animations provide an enjoyable solution in the era of digital learning.